How to keep well in wartime - Great Britain. Ministry of Health ; Central Council for Health Education (Great Britain); Clegg, Hugh Anthony, 1900- (London : His Majesty's Stationery Office, 1943)
1943 1943 1940s 28 pages : illustrations HOW TO KEEP WELL IN WARTIME and drinking too much are often due to "nervousness". The act of smoking seems to relieve a sense of strain — and in wartime everyone is living under some sort of strain. But, in excess, smoking makes the nervousness worse, apart from its harm to physical health. The effect of alcohol on the brain is to relieve stress and anxiety. As everyone knows, it makes a person less critical — of himself at all events. But the slave to drink gradually undergoes moral and physical degeneration. In wartime it is inevitable that people should seek relief from strain : and there is nothing to be said against the occasional drink taken in moderation. The world would be a dull and colourless place if it were inhabited entirely by plaster saints eating dry bread and taking sips of plain water. Health and Moral Responsibility. In wartime young men and young women are thrown into situations that encourage excess. The atmosphere of war is itself unhealthy, however much heroism it may bring out in people. Waste of lives, waste of materials, waste of money, however necessary these evils may be for the time, encourage a spirit of "Eat, drink, and be merry, for to-morrow we die". There is much less of this spirit in Great Britain to-day than in the last war. We are more aware this time that what we are fighting against is evil. Each man knows that he is fighting for the freedom of others as well as for his own. This growing sense of personal responsibility of each man and woman is one of the good things that has come out of the war. There is one thing that can knock this sense of responsibility sideways, and that is a "drop too much" of alcohol. A doctor has no desire to moralize about this, or to preach a sermon about it. His concern is with health, and ill-health or disease. He knows, for example, that the occasional "binge" often leads to an occasional "night out" between a man and a woman who, under the temporary influence of alcohol, lose their sense of responsibility. The doctor knows, too, that casual sexual relations often end up in venereal disease. Or to put it in another way, he knows that venereal disease is almost always the result of promiscuous sexual relationships. The Causes of Venereal Disease. Although he cannot ignore the moral aspect of the question, the doctor is chiefly concerned about the effect of venereal disease on health and happiness. He knows that it is the source of untold misery. It would not be so bad if venereal disease affected only the person who caught it. The personal loss of health and efficiency is a severe penalty, but venereal disease may affect the unborn generation. The child of a parent with venereal disease may become blind, paralysed, crippled in mind and body, a pathetic and tragic witness to the irresponsibility of its father or its mother. Let us be clear what venereal disease is. It is an infection, just as the common cold and pneumonia are infections. An infection is an 14 420/BS/7/16/18